PENGARUH DEBT TO EQUITY RATIO (DER), RETURN ON ASSET (ROA), EARNING PERSHARE (EPS), PRICE EARNING RATIO (PER) TERHADAP RETURN SAHAM PADA PERUSAHAAN JASA PERHOTELAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sinaga, Ria Veronica (Jurnal Manajemen dan Bisnis, 2019)
This study aims to determine the effect of Debt to Equity Ratio (DER), Return On Assets (ROA), Earning Per Share (EPS), Price Earning Ratio (PER) to Return of Stock at Hospitality Services Company listed on Indonesia Stock Exchange. The benefits of research is to provide information material to investors in making investment decisions. The number of companies to be sampled are 5 Hospitality Services Companies, namely: Bayu Buana Tbk (BAYU), Fast Food Indonesia Tbk (FAST), Grahamas Citrawisata Tbk (GMCW), Destination Tirta Nusantara Tbk (PDES), and Golden Eagle Energy Tbk SMMT). In this study used secondary data that is Financial Statements Hospitality Services Companies listed in Indonesia Stock Exchange 2010-2013 period that can be accessed via the internet. Method of data analysis used is multiple regression analysis (multiple regression analysis). Based on the result of research, the regression equation is obtained as follows: Return = 0,979 - 0,438 DER - 0,093 ROA + 0,002 EPS + 0,002 PER indicate that DER variable variable have negative and insignificant influence, ROA variable has negative and significant influence, EPS variable has positive and significant effect, and variable of PER have positive and insignificant effect to stock return. DER, ROA, EPS and PER simultaneously affect the stock return of hotel services company. value adjusted R2 of 0.909. This means that 90.9 percent of stock return variables can be explained by variations of DER, ROA, EPS and PER variables while the remaining 9.1 percent is explained by other variables outside the model.